Implementation Of Police Role In Countermeasures Of Traffic Criminal Acts Of Traffic Violations In Efforts To Establish Police Images As Community Guidelines - Riyanto Riyanto; Umar Ma'ruf; Sri Kusriyah Kusriyah (Jurnal Daulat Hukum, 2020)
This study aims to determine the implementation of the role of the police in traffic criminal acts of traffic violations in an effort to build the image of the police as a community protector and inhibiting factors and solutions. The method used is sociological juridical, descriptive analytical research specifications. The data used are primary data and secondary data. Data collection methods are field studies and library studies. The data analysis method uses qualitative analysis. As a knife of analysis, crime prevention theory and law enforcement theory are used. The results showed that the implementation of the role of the police in tackling traffic violations in an effort to build the image of the police as a community protector was carried out through preemptive, preventive and repressive efforts. Pre-emptive efforts are carried out through socialization activities whose main purpose is to instill moral values in society to obey the law. Preventive efforts are carried out through operations or patrols to prevent traffic violations. While repressive efforts carried out through actions in the form of reprimands or tickets to violators. Inhibiting factors in implementing the role of the police in tackling traffic violations in an effort to build an image as a community protector are the lack of professionalism of the traffic police, the legal awareness of the community is still low, and there is a culture of lawlessness from the community.Keywords: The Role Of The Police; Criminal Acts; Traffic Violations.